Poly-acrylonitrile-based gel-polymer electrolytes for sodium-ion batteries - Vignarooban, K.; Badami, P.; Dissanayake, M.A.K.L.; Ravirajan, P.; Kannan, A.M. (University of Jaffna, 2017)
Research and development activities on sodium ion batteries are becoming prominent in the past few years. Compared to lithium-based batteries, the sodium-based batte ries will be cheaper because of the abundancy of sodium raw materials in the earth’s crust and also in seawater. In the cur rent study, we synthesized and characterized poly-acrylonitrile (PAN)-based gel-polymer electrolytes formed with NaClO4 and dissolved in ethylene carbonate (EC) and propylene car bonate (PC). By systematically varying the weight ratios of polymer, salt, and the solvents, we obtained an optimum room temperature ionic conductivity of 4.5 mS cm−1 for the com position 11PAN-12NaClO4-40EC-37PC (wt.%), which is rea sonably good for practical applications. This value of conduc tivity is comparable to a few other Na+ ion conducting gel polymer electrolyte systems studied in the recent past. Variation of ionic conductivity with inverse temperature showed Arrhenius behavior. Activation energies estimated for all the samples showed only a slight variation suggesting that a single activation process which depends on the EC/PC co-solvent governs the ionic mobility in these gel-polymer
Keywords: Gel-polymer electrolytes; Sodium-ion batteries; Ionic conductivity; Impedance analysis